LiO-t-Bu/CsF-Mediated Formal Hydrolysis of Trifluoromethyl Arenes - Shigeno, Masanori; Kiriyama, Moe; Izumi, Koki; Sasaki, Keita; Sasamoto, Ozora; Nozawa-Kumada, Kanako; Kondo, Yoshinori (Synthesis, 2024)
This study investigates the formal hydrolysis of trifluoromethyl arenes without deprotonation functionality utilizing a combined Brønsted base system comprising LiO-t-Bu and CsF. The reaction conditions were optimized using 4-(trifluoromethyl)biphenyl as the model substrate, achieving a 94% yield with LiO-t-Bu/CsF. The scope of the substrate was explored, demonstrating the applicability of the system to various functionalities, such as (hetero)aryl, tert-butyl, methyl, amide, and alkenyl moieties. Mechanistic insights suggest a single electron transfer process.
Keywords: trifluoromethyl arene; hydrolysis; combined Brønsted base; single-electron transfer; aromatic carboxylic acid